The Impact of Education on Knowledge of Household Waste Management in Semerap Village, Kerinci Regency - Irmayanti, VA; Ariyadi, Bambang; Erris, Erris (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Waste management aims to improve public health and environmental quality and can convert waste into resources. Waste management is said to be good if the waste does not become a medium for the breeding of disease germs and does not become an intermediary for the spread of disease. The housewife is a central and very important figure in running life in the family. The women's empowerment program is directed at improving the quality of life of women and the active participation of women in society in preventing and controlling the impact of pollution as well as good and correct environmental management, especially in terms of waste management. This type of research includes a quasi-experiment using a one group pre-test and post-test design and the respondents in this research are housewives. The average knowledge analysis before being given education was 8.74% with a standard deviation of 1.450%. In terms of knowledge, the average obtained is 9.68% with a standard deviation of 2.143%. It can be seen that the mean value of the difference in knowledge before and after being given education is 0.943 with a standard deviation of 1.324. The statistical test results obtained a p-value of 0.000 so it can be concluded that there is a significant influence between knowledge before and after providing maternal education about waste management.